Examination of IgG Fc Receptor CD16A and CD64 Expression by Canine Leukocytes and Their ADCC Activity in Engineered NK Cells - Hullsiek, Robert; Li, Yunfang; Snyder, Kristin M.; Wang, Sam; Di, Da; Borgatti, Antonella; Lee, Chae; Moore, Peter F.; Zhu, Cong; Fattori, Chiara; Modiano, Jaime F.; Wu, Jianming; et al. (Frontiers in Immunology, 2022)
Human natural killer (NK) cells can target tumor cells in an antigen-specific manner by the recognition of cell bound antibodies. This process induces antibody-dependent cell-mediated cytotoxicity (ADCC) and is exclusively mediated by the low affinity IgG Fc receptor CD16A (FcγRIIIA). Exploiting ADCC by NK cells is a major area of emphasis for advancing cancer immunotherapies. CD64 (FcγRI) is the only high affinity IgG FcR and it binds to the same IgG isotypes as CD16A, but it is not expressed by human NK cells. We have generated engineered human NK cells expressing recombinant CD64 with the goal of increasing their ADCC potency. Preclinical testing of this approach is essential for establishing efficacy and safety of the engineered NK cells. The dog provides particular advantages as a model, which includes spontaneous development of cancer in the setting of an intact and outbred immune system. To advance this immunotherapy model, we cloned canine CD16A and CD64 and generated specific mAbs. We report here for the first time the expression patterns of these FcγRs on dog peripheral blood leukocytes. CD64 was expressed by neutrophils and monocytes, but not lymphocytes, while canine CD16A was expressed at high levels by a subset of monocytes and lymphocytes. These expression patterns are similar to that of human leukocytes. Based on phenotypic characteristics, the CD16A+ lymphocytes consisted of T cells (CD3+ CD8+ CD5dim α/β TCR+) and NK cells (CD3− CD5− CD94+), but not B cells. Interestingly, the majority of canine CD16A+ lymphocytes were from the T cell population. Like human CD16A, canine CD16A was downregulated by a disintegrin and metalloproteinase 17 (ADAM17) upon leukocyte activation, revealing a conserved means of regulation. We also directly demonstrate that both canine CD16A and CD64 can induce ADCC when expressed in the NK cell line NK-92. These findings pave the way to engineering canine NK cells or T cells with high affinity recombinant canine CD64 to maximize ADCC and to test their safety and efficacy to benefit both humans and dogs.